THE PROSPECT OF DIGITALLY ENHANCED COLORIMETRY AS AN ANALYTICAL METHOD FOR WATER QUALITY DETERMINATION - Rijal Hakiki; Temmy Wikaningrum (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
Aim: This study aims to observe the potential implementation of analytical methods based on digital image processing as an alternative method of colorimetric analysis that can be implemented in site. Methodology and Results: Pt-Co standard series solutions at concentrations of 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 concentration units (CU) were measured by spectrophotometric method and digitally enhanced colorimetric (DEC) method to obtain a response in the form of absorbance (Abs) and area under curve (AUC) value. Absorbance measurement was carried out at 317.5 nm (λ max). The AUC value was obtained from the 3-point RGB value measurements, made average so that a color band is produced, then quantified by translating the color band intensity into the response curve in ImageJ software. The Abs and AUC values of artificial samples are processed into CU values with linear equations resulting from linear regression test. The results of the calculation of CU values from the two measurement methods were tested using independent t test method to examine significant differences between the two measurement methods. Conclusion, significance and impact study: Coefficient of determination (R2) plot CU VS AUC = 0.8638, in independent t test was obtained p-value = 0.4246 at the 95% confidence level. Therefore, it can be concluded that digitally enhanced colorimetric could be used to determine water quality, especially color parameter in site measurement.